Herpes simplex encephalitis relapse with chorea is associated with autoantibodies to N‐Methyl‐D‐aspartate receptor or dopamine‐2 receptor. Issue 1 (1st October 2013) - Mohammad, Shekeeb S.; Sinclair, Kate; Pillai, Sekhar; Merheb, Vera; Aumann, Tim D.; Gill, Deepak; Dale, Russell C.; Brilot, Fabienne
ABSTRACT Background Movement disorder relapses after herpes simplex virus 1 (HSV1) encephalitis have been hypothesized to be secondary to postviral autoimmunity. Recently, a proportion of patients with HSV1 encephalitis (HSE) were shown to produce autoantibodies against N‐methyl‐D‐aspartate receptor (NMDAR). Methods We measured autoantibodies against NMDAR and dopamine‐2 receptor (D2R) expressed at the cell surface in the stored acute serum of 9 children with HSE, 3 of whom had a relapsing course with chorea. Results The 3 patients with chorea had elevated autoantibodies against NMDAR (n = 1), D2R (n = 1), or both (n = 1), whereas patients without chorea were negative (n = 6). The prospectively identified patient with chorea and NMDAR autoantibodies improved after early treatment with steroids, intravenous immunoglobulin, and cyclophosphamide, with reduction in serum NMDAR antibody titers. Conclusions These autoantibody findings lend support to the autoimmune hypothesis and the early use of immune suppression in post‐HSE chorea. © 2013 International Parkinson and Movement Disorder Society